Efficacy of Different Rhizobium Strains of Forest Trees Species on Albizia lebbek - Dadwal, Jamaluddin V. S.; Chouhan, J. S. (Indian Forester, 1995)
The efficacy of pure culture of Rhizobium strains of different forest tree species viz. Dalbergia sissoo, Leucaena leucocephala, Pongamia pinnata and Albizia lebbek was tested on the growth of Albizia lebbek seedlings. The experiment was conducted in the nursery upto 3 months. It was noticed that the shoot length, girth of seedlings, number of nodules, fresh and dry weight and nitrogen content of Albizia lebbek seedlings increased to a considerable extent upon incoculation with the Rhizobium strain isolated from Albizia lebbek than with Rhizobium strains of other legume species. This indicated that Rhizobium is selective for the host.